Characterizations of InN Thin Films Grown on Si (110) Substrate by Reactive Sputtering - Amirhoseiny, M.; Hassan, Z.; Ng, S. S.; Ahmad, M. A. (Hindawi Publishing Corporation, 2011)
Indium nitride (InN) thin films were deposited onto Si (110) by reactive sputtering and pure In target at ambient temperature. The effects of the Ar–N2 sputtering gas mixture on the structural properties of the films were investigated by using scanning electron microscope, energy-dispersive X-ray spectroscopy, atomic force microscopy, and X-ray diffraction techniques. The optical properties of InN layers were examined by micro-Raman and Fourier transform infrared (FTIR) reflectance spectroscopy at room temperature. Structural analysis specified nanocrystalline structure with crystal size of 15.87 nm, 16.65 nm, and 41.64nm for InN films grown at N2/Ar ratio of 100/0, 75/25, and 50/50, respectively. The Raman spectra indicates well defined peaks at 578, 583, and 583 cm−1, which correspond to the A1(LO) phonon of the hexagonal InN films grown at gas ratios of 100 : 0, 75 : 25 and 50 : 50 N2 : Ar, respectively. Results of FTIR spectroscopy show the clearly visible TO [E1(TO)] phonon mode of the InN at 479 cm−1 just for film that were deposited at 50 : 50 N2 : Ar. The X-ray diffraction results indicate that the layers consist of InN nanocrystals. The highest intensity of InN (101) peak and the best nanocrystalline InN films can be seen under the deposition condition with N2/Ar gas mixture of 50 : 50.